1961
DOI: 10.1172/jci104409
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Plasma Free Fatty Acids Into Plasma Triglycerides in Man*

Abstract: Plasma triglycerides (neutral fat) may be divided into 1) that portion which is present during the fasting state and 2) that which, after ingestion of fat, is added to and temporarily augments the fasting level of triglycerides.The present investigation deals with the relationship of plasma free fatty acids (plasma FFA) to fasting plasma triglycerides (plasma TG) in man. From these observations a quantitative assessment of the amount of plasma FFA converted to plasma TG will be presented. The data also permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

1962
1962
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…Therefore, some FFA tracer stored in visceral fat may have arrived via the VLDL-TG/LPL pathway, although our results suggest that the contribution of this pathway was probably small. First, in the palmitate protocol, we found that only ϳ4% of the FFA tracer traversed the VLDL-TG pool over 4.5-9.5 h, which is consistent with previous reports (18,30). This was accompanied by a small and nonsignificant increase in FFA tracer accumulation in subcutaneous fat from 30 -45 min to 24 h after the tracer bolus (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, some FFA tracer stored in visceral fat may have arrived via the VLDL-TG/LPL pathway, although our results suggest that the contribution of this pathway was probably small. First, in the palmitate protocol, we found that only ϳ4% of the FFA tracer traversed the VLDL-TG pool over 4.5-9.5 h, which is consistent with previous reports (18,30). This was accompanied by a small and nonsignificant increase in FFA tracer accumulation in subcutaneous fat from 30 -45 min to 24 h after the tracer bolus (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…For practical purposes, we used different FFA tracers in two protocols: the oleate protocol and the palmitate protocol. The two tracers should give comparable results because they give similar estimates of plasma FFA kinetics (16) and have similar fractional extraction across adipose tissue (17) and similar incorporation into plasma triglycerides (18). Because these two fatty acids are the major fatty acids found in plasma, their metabolism can be taken to be representative of the bulk of plasma FFA.…”
Section: Methodsmentioning
confidence: 99%
“…These values are comparable to those of l~riedberg et al [21] who used an integration method and those reported by Reaven et al [41], and Nflddli/and Kekki [37] who used the atI glycerol labelling technique. These results encouraged us to use the endogenous labelling technique for its simplicity and convenience.…”
Section: *supporting
confidence: 88%
“…Friedberg et al 10 have already shown a good correlation between triglycerides and fatty acids in the circulation. Baseline blood pressure and heart rate before ILH infusion were similar in both groups.…”
Section: Discussionmentioning
confidence: 89%